1991
DOI: 10.7164/antibiotics.44.693
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic GE2270 A: A novel inhibitor of bacterial protein synthesis. I. Isolation and characterization.

Abstract: Anovel antibiotic, GE2270A, was isolated from the fermentation broth of a strain of Planobispora rosea. The product was found to inhibit bacterial protein synthesis. Structural characteristics showed similarities between GE2270 A and thiazolyl peptides such as micrococcin which is known to inhibit protein synthesis by acting directly on the ribosome. Despite this similarity GE2270A showed functional analogy to kirromycin-like antibiotics and pulvomycin, as its molecular target was found to be elongation factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
0
6

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(99 citation statements)
references
References 52 publications
4
88
0
6
Order By: Relevance
“…17 Consistent with our screening results, we found that the MIC against B. cenocepacia and B. vietnamiensis was 8 mg ml À1 . The purified molecule also exerted activity (MICs of 16-32 mg ml À1 ) against P. aeruginosa and Acinetobacter baumannii (ATCC 17978), two other opportunistic pathogens that are highly antibiotic resistant.…”
Section: Biochemical Characterization Of the Induced Secondary Metabosupporting
confidence: 89%
“…17 Consistent with our screening results, we found that the MIC against B. cenocepacia and B. vietnamiensis was 8 mg ml À1 . The purified molecule also exerted activity (MICs of 16-32 mg ml À1 ) against P. aeruginosa and Acinetobacter baumannii (ATCC 17978), two other opportunistic pathogens that are highly antibiotic resistant.…”
Section: Biochemical Characterization Of the Induced Secondary Metabosupporting
confidence: 89%
“…GE2270 is a novel potent antibiotic inhibiting protein synthesis in Gram-positive bacteria (Goldstein et al, 1993;Selva et al, 1991). It is the natural precursor of clinical candidate BI-K0376 specifically active against Propionibacterium acnes, including isolates resistant to currently available therapies (Jabes et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…l), in the nature of their interaction with EF-Tu (Fasano et al, 1978;Wolf et al, 1974;Anborgh & Parmeggiani, 1991) and in their spectrum of antibacterial activity (Selva et al,199 1). All three antibiotics are natural products : kirromycins and pulvomycin are produced by different species of Streptomyces, MDL 62 879 by Planobispora rosea (Parmeggiani & Swart, 1985;Akita et al, 1963;Selva et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…MDL 62879 is active against Grampositive bacteria (Selva et al, 1991). Kirromycins are not active against some species of Gram-positive bacteria such as Bacillus subtilis, staphylococci and enterococci, but they are active against some Gram-negative bacteria such as Neisseria gonorrhoeae and Haemophilus influenzae (Frost et al, 1976(Frost et al, , 1979 on which MDL 62879 has little or no activity.…”
Section: Introductionmentioning
confidence: 99%